English in The BRICS Eclipse: Learning Beyond Empire - Iskandarsyah Siregar; Awang Azman Awang Pawi (Yayasan Darussalam Bengkulu, 2025)
This study examines the changing ideological and pedagogical position of English in the context of BRICS expansion, particularly as the bloc increasingly represents a multilingual, multipolar, and Global South-oriented geopolitical formation. Rather than assuming that English is declining, this article argues that English is being re-semiotized from an imperial centre-language into a negotiated bridge-language for diplomacy, education, scientific circulation, trade, technological exchange, and intercultural communication. Employing a multidisciplinary mixed-methods approach, the study integrates sociolinguistics, World Englishes, English as a Lingua Franca, linguistic imperialism, linguistic capital theory, critical discourse analysis, and geopolitical interpretation. The data were drawn from institutional BRICS documents, global English proficiency indicators, and public geopolitical discourse from 2024–2026, including the period of Indonesia’s full membership in BRICS. The findings show that English remains a powerful form of linguistic capital, yet its symbolic authority is no longer exclusively anchored in Anglophone Western institutions. Institutional and economic data demonstrate the growing demographic and purchasing-power-parity weight of BRICS, while English proficiency data reveal uneven linguistic capital among member states. Qualitative discourse evidence further indicates that BRICS discourse foregrounds multilateralism, governance reform, development, sovereignty, cultural plurality, and South–South cooperation rather than Anglocentric imitation. This study concludes that English in the BRICS eclipse is not “less English” but “different English”: globally functional, strategically necessary, and ideologically repositioned. The implication is that English education in BRICS societies and partner countries should move beyond native-speaker dependency by integrating linguistic accuracy, intercultural intelligibility, discourse-critical awareness, geopolitical literacy, multilingual comparison, and epistemic sovereignty.